PENGISIAN KEKOSONGAN JABATAN WAKIL KEPALA DAERAH YANG BERASAL DARI PARTAI POLITIK ATAU GABUNGAN PARTAI POLITIK BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2008 - Tjokorda Alit Budi Wijaya; I Made Subawa; Ni Made Ari Yuliartini Griadhi (Kertha Negara : Journal Ilmu Hukum, 2014)
The fulfillment vacancy of Deputy Head of Regional from a Political Party orCoalition of Political Parties in several regions in Indonesia are often impressed allowedto drag filling by the authority holder particularly Regional Head along with thelegislature, although in essence the rules on charging mechanism of vacancy of the DeputyHead of Regional has been regulated in the written on law of Republic Indonesia Number12 year 2008 and supported by some of the legislation below. Therefore, this study willexplain how to fill the vacancy mechanism Deputy Head of Region from the political partyor coalition of political parties according to Regulation Legislation applicable. This studyalso explains that the filling of vacant position of Deputy Head of Region is still required inthe Regional Government system.